2006
DOI: 10.1097/01.fjc.0000232063.87708.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hct on L-NAME-induced Potentiation of Anaphylactic Presinusoidal Constriction in Perfused Rat Livers

Abstract: Effects of hematocrit (Hct) on N-nitro-L-arginine methyl ester (L-NAME)-induced modulation of anaphylactic venoconstriction were determined in isolated perfused rat livers. The rats were sensitized with ovalbumin (1 mg), and the livers were excised 2 weeks later and perfused portally and recirculatingly under constant flow at Hct of 0%, 5%, 16%, and 22%. The hepatic sinusoidal pressure was estimated via the double occlusion pressure (Pdo), and the presinusoidal resistance (Rpre) and the postsinusoidal resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…We previously showed that almost selective presinusoidal contraction is the characteristic for the hepatic anaphylaxis of isolated SD rat livers perfused with blood (27) or blood-free perfusate (8). We confirmed this previous finding in the present experiment on isolated SD rat livers perfused with ovalbuminKrebs solution.…”
Section: Discussionsupporting
confidence: 82%
“…We previously showed that almost selective presinusoidal contraction is the characteristic for the hepatic anaphylaxis of isolated SD rat livers perfused with blood (27) or blood-free perfusate (8). We confirmed this previous finding in the present experiment on isolated SD rat livers perfused with ovalbuminKrebs solution.…”
Section: Discussionsupporting
confidence: 82%
“…12 In the present study, exercise training attenuated anaphylaxisinduced venoconstriction of the isolated liver, although anaphylactic venoconstriction of isolated perfused livers from exercise-trained rats as well as sedentary control rats was augmented by L-NAME, which is consistent with previous results. 23,24 Exercise-induced attenuation of anaphylactic venoconstriction seems to be independent of NO, because L-NAME did not eliminate this effect of exercise. The mechanism underlying the exercise training-induced attenuation of anaphylactic presinusoidal constriction of perfused livers is not known.…”
Section: Discussionmentioning
confidence: 99%